TENDENCY OF MOTORCYCLE TRAFFIC VIOLATIONS AND ACCIDENTS BASED ON A VARIETY OF DRIVING LICENSE OWNERSHIP - Prabowo, Hendro; P. Dewi, Mahargyantari; Sulthoni, Muhammad Ihsan; Salve, Henny Regina; Afandi, Nur Aziz; Marissa, Aski; Dewi, Dinar Sari Eka; Hartatik; Firdaus, Mu’minatus Fitriati; Kusumastuti, Astri Nur; Sanjaya, Sang Putu Adi; Mardika, I Gusti Ngurah Anom; Wijaya, Ade; Ismayenti, Lusi; Primadewi, Chatarina Fiertrika (Prodi Teknik Sipil, Fakultas Teknik, Universitas Jember dan Forum Studi Transportasi antar Perguruan Tinggi, 2023)
Indonesia is a country with the number of motorcycles reaching 43.34% of the total population or 119.5 million motorcycles compared to 275.7 million people. However, the number of Driver's License holdings is only 8.8 million (8.3%). This study aims to determine the tendency of violations and traffic accidents among motorcyclists related to the ownership of a Driver's License of various ages in several cities in Indonesia. With a statistical descriptive research method using online questionnaires, this study found a tendency to violations and traffic accidents based on the ownership of a Driver's License. But there was no difference between the two groups after testing with statistics in both traffic violations and traffic accidents. ABSTRAK Indonesia merupakan negara dengan jumlah sepeda motor mencapai 43,34% dari jumlah penduduk atau 119,5 juta sepeda motor dibandingkan 275,7 juta penduduk. Namun, jumlah kepemilikan SIM C hanya 8,8 juta (8,3%). Penelitian ini bertujuan untuk mengetahui kecenderungan pelanggaran dan kecelakaan lalu intas pada pengendara sepeda motor berkaitan dengan kepemilikan SIM C dari beragam usia di beberapa kota di Indonesia. Dengan metode penelitian deskriptif statistik yang menggunakan kusioner online, penelitian ini menemukan adanya kecenderungan pelanggaran dan kecelakaan lalu intas berdasarkan kepemilikan SIM C. Namun tidak ada perbedaan di antara kedua kelompok setelah diuji dengan statistik baik dalam pelanggaran lalu lintas maupun kecelakaan lalu lintas.